Parametrizing Nonbonded Interactions Between Silica and Water From First Principles - Özçelik, H. Gökberk; Barışık, Murat; Sözen, Yiğit; Sözen, Yiğit; Şahin, Hasan; Şahin, Hasan; Barışık, Murat (Elsevier, 2020)
Silica has been used in a vast number of micro/nano-fluidic technologies where interactions of water with silica at the molecular level play a key role. In such small systems, an understanding of mass and heat transport or surface wetting relies on accurate calculations of the water-silica interface coupling through atomic interactions. Molecular dynamics (MD) is a convenient tool for such use, but force field parameters for nonbonded interactions are required as an input, which are very limited in literature. These interaction parameters can be predicted by density functional theory, but dispersion forces are not calculated in standard models for electron correlations that additional correction models have been proposed at different levels of sophistications, and still under development. Accordingly, this work employs state of the art quantum chemistry to compute the binding energies. Force field parameters for silica/water van der Waals interactions were calculated, and later tested in MD simulations of water droplet on silica surface. While the standard dispersion corrections overestimated the binding energy, Becke-Johnson model yielded interactions parameters recovering experimentally measured wetting behavior of silica with a water contact angle of approximately 12.4 degrees on the flat and clean silica surface. Results will be useful for the current molecular modelling attempts by providing transferable parameters for simple silica/water van der Waals interactions as an alternative to existing complex surface interaction models.
Keywords: Density functional theory; Becke-Johnson model; Molecular dynamics; Surface wetting